Thermodynamic properties of semiclassical fully ionized hydrogen plasma - Gabdullin, M. T.; Ismagambetova, T. N. (Recent Contributions to Physics, 2013)
In this work a fully ionized hydrogen plasma consisting of electrons and ions is described. The numberdensity varies in the range and the temperature domain considered here is . The semiclassical interaction potentials, taking into account the quantum-mechanicaldiffraction and symmetry effects at short distances, were used for the investigation of such plasma’s properties. The screening effect was taken into account by using numerical solution of the Ornstein-Zernike equation in HNC approximation. This equation relates the full and direct correlation functions with pair interaction potential of the particles. When considering radial distribution functions it was turn out that symmetry effect had a greater impact on particles’ interaction for more dense plasma at small distances. On the basis of semiclassical interaction potentials and radial distribution functions the thermodynamic properties of nonideal hydrogen plasma (internal energy and equation of state) were calculated. Due to the quantummechanical effect of symmetry interaction between charged particles weakens what leads to increase in the correlation energy and the pressure of plasma
Keywords: semiclassical interaction potentials; radial distribution functions; thermodynamic characteristics